Efficient synthesis for large-scale production and characterization for hydrogen storage of ligand exchanged MOF-74/174/184-M (M = Mg2+, Ni2+). (12th January 2017) - Oh, Hyunchul; Maurer, Stefan; Balderas-Xicohtencatl, Rafael; Arnold, Lena; Magdysyuk, Oxana V.; Schütz, Gisela; Müller, Ulrich; Hirscher, Michael
Abstract: A semitechnical route (optimized by BASF SE) to synthesize MOF-74/174-M (M = Mg 2+, Ni 2+ ) efficiently in ton-scale production is presented with the goal of mobile and stationary gas storage applications especially for hydrogen as future energy carrier. In addition, a new member of these series of materials, MOF-184-M (M = Mg 2+, Ni 2+ ) is introduced using ligand exchange strategy in order to produce a more porous analogue (possessing large aperture) without loss of crystallinity. This family comprising MOF-74/174/184 are characterized systematically for hydrogen adsorption properties by volumetric measurements with a Sieverts' apparatus. Replacing the linker by a longer one results in an increase of the BET area from 984 to 3154 m 2 /g and an enhancement of the excess cryogenic (77 K) hydrogen storage capacity from 1.8 to 4.7 wt%. The heat of adsorption of linker exchanged MOF-174/184 (as a function of uptake) shows similar values to the parent MOF-74, indicating successful construction of expanded MOFs in large scale production. Finally, a usable capacity of these MOFs is investigated for mobile application, revealing that the increasing surface area without strong binding metal sites through longer linker exchange is one of important parameters for improving usable capacity. Graphical abstract: Highlights: A large-scale synthesis method for MOF-74/74(II) have been introduced. A newly developed large pore MOF-184 is synthesized by a ligand exchange strategy. Replacing a linker by longer one shows enhanced BET area and H2 storage capacity. Usable capacity is improved by increasing BET area w/o strong binding sites.